Cold storage and cryopreservation of tick cell lines - Lallinger, Gertrud (BioMed Central, 2010)
BACKGROUND: Tick cell lines are now available from fifteen ixodid and argasid species of medical and veterinary importance. However, some tick cell lines can be difficult to cryopreserve, and improved protocols for short- and long-term low temperature storage will greatly enhance their use as tools in tick and tick-borne pathogen research. In the present study, different protocols were evaluated for cold storage and cryopreservation of tick cell lines derived from Rhipicephalus (Boophilus) decoloratus, Rhipicephalus (Boophilus) microplus, Ixodes ricinus and Ixodes scapularis. For short-term cold storage, cells were kept under refrigeration at 6°C for 15, 30 and 45 days. For cryopreservation in liquid nitrogen, use of a sucrose-phosphate-glutamate freezing buffer (SPG) as cryoprotectant was compared with dimethylsulfoxide (DMSO) supplemented with sucrose. Cell viability was determined by the trypan blue exclusion test and cell morphology was evaluated in Giemsa-stained cytocentrifuge smears. RESULTS: Cold storage at 6°C for up to 30 days was successful in preserving R. (B.) microplus, R. (B.) decoloratus, I. ricinus and I. scapularis cell lines; lines from the latter three species could be easily re-cultivated after 45 days under refrigeration. While cell lines from all four tick species cryopreserved with 6% DMSO were successfully resuscitated, the R. (B.) decoloratus cells did not survive freezing in SPG and of the other three species, only the R. (B.) microplus cells resumed growth during the observation period. CONCLUSIONS: This constitutes the first report on successful short-term refrigeration of cells derived from R. (B.) decoloratus, R. (B.) microplus, and I. ricinus, and use of SPG as an alternative to DMSO for cryopreservation, thus making an important contribution to more reliable and convenient tick cell culture maintenance.